2014
DOI: 10.1002/vnl.21439
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of chlorinated polyvinylchloride with acrylonitrile-butadiene-styrene graft copolymers

Abstract: In this article, a series of acrylonitrile‐butadiene‐styrene (ABS) graft copolymers with polybutadiene (PB) particle sizes ranging from 66 nm to 304 nm were prepared. Toughening of chlorinated polyvinylchloride (CPVC) with ABS graft copolymers was investigated. The results showed that PVC, as a compatibilizer, made the miscibility of CPVC/ABS blends better. PB particle size had significant influence on the ductility of CPVC/ABS blends. There was obvious synergetic effect in the bimodal system. From scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it is expected that ASA terpolymer can also work as an impact modifier for rigid PVC. Ren and coworkers studied the effect of AN content in SAN shell on the toughness of PVC/ASA binary blends and PVC–ASA–DOP blends. They found that the impact strength of the PVC/ASA blends and PVC–ASA–DOP blends increased and then decreased with the increasing AN content in the SAN shell.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is expected that ASA terpolymer can also work as an impact modifier for rigid PVC. Ren and coworkers studied the effect of AN content in SAN shell on the toughness of PVC/ASA binary blends and PVC–ASA–DOP blends. They found that the impact strength of the PVC/ASA blends and PVC–ASA–DOP blends increased and then decreased with the increasing AN content in the SAN shell.…”
Section: Introductionmentioning
confidence: 99%